Analysis and identification of m6A RNA methylation regulators in metastatic osteosarcoma - Hanji Huang; Xiaofei Cui; Xiong Qin; Kanglu Li; Guohua Yan; Dejie Lu; Mingjun Zheng; Ziwei Hu; Danqing Lei; Nihan Lan; Li Zheng; Zhenchao Yuan; et al. (Elsevier, 2022)
Osteosarcoma (OS) is characterized by rapid growth and early metastasis. However, its mechanism remains unclear. N6-methyladenosine (m6A) modification and its regulatory factors play essential roles in most cancers, including OS. In this study, we screened out 21 m6A modifiers using the Therapeutically Applicable Research to Generate Effective Treatments (TARGET) database, followed by the identification of the critical m6A methylation modifiers. The results revealed that the expression levels of three m6A methylation regulators, namely RBM15, METTL3, and LRPPRC, were associated with the low survival rate of patients with OS. We further studied the independent prognostic factors by performing univariate and multivariate Cox analyses and found that metastasis was an independent prognostic factor for patients with OS. Furthermore, we found for the first time that RBM15 was specific for metastatic OS rather than non-metastatic OS. Moreover, the significant overexpression of RBM15 was validated in metastatic OS cell lines and in actual human clinical specimens. We also revealed that RBM15 promoted the invasion, migration, and metastasis of OS cells through loss-functional and gain-functional experiments and an animal metastatic model. In conclusion, RBM15 has a high correlation with OS metastasis formation and the decreased survival rate of patients with OS, and this may serve as a useful biomarker for predicting metastasis and prognosis of patients with OS.